A Whole School Agreement: Professional Learning with a Focus on Environmental STEM. (2nd January 2022) - Livers, Stefanie D.
ABSTRACT: Science, technology, engineering, and mathematics (STEM) education is important to producing students prepared for problem solving, critical analysis, and collaborative approaches to address the needs of the 21st century. For meaningful and intentional STEM instruction to occur, teachers need support and professional development. This paper presents a case study of a year-long professional learning project connecting the school's environmental science focus to improving mathematics instruction. A whole school agreement bounds this particular case. The school faculty initiated the project and included developing a mathematics trail to connect with their nature trail, garden, and an outdoor amphitheater. The quantitative and qualitative data reveal significant changes in mathematics practices and teachers' beliefs about the teaching and learning of mathematics. Since this case study revealed that whole school professional development in STEM could improve the teaching and learning of mathematics, implications for practice and research are discussed.